2005
DOI: 10.1038/nmat1550
|View full text |Cite
|
Sign up to set email alerts
|

Study of colloidal quantum-dot surfaces using an innovative thin-film positron 2D-ACAR method

Abstract: Nanosized inorganic particles are of great interest because their electronic properties can be easily tailored, providing a tremendous potential for applications in optoelectronic devices, light-emitting diodes, solar cells and hydrogen storage. Confinement of electrons and holes to dimensions comparable to their wavelength leads to quantum-well states with modified wavefunctions and density of states. Surface phenomena are crucial in determining nanoparticle properties in view of their large surface-to-volume… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
91
2

Year Published

2007
2007
2018
2018

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 66 publications
(97 citation statements)
references
References 25 publications
2
91
2
Order By: Relevance
“…This value is obtained experimentally using energy dispersive x-ray spectroscopy. In theory, we assume the CdSe system is in an 1:1 atomic ratio for symmetry and simplicity, although it has been shown the stoichiometry of CdSe QDs is not quite 1:1 13,14 . Using the known particle sizes and packing fractions, we can obtain the number of Cd atoms present in the QD to obtain an expression for C in terms of measured values…”
Section: Theorymentioning
confidence: 99%
“…This value is obtained experimentally using energy dispersive x-ray spectroscopy. In theory, we assume the CdSe system is in an 1:1 atomic ratio for symmetry and simplicity, although it has been shown the stoichiometry of CdSe QDs is not quite 1:1 13,14 . Using the known particle sizes and packing fractions, we can obtain the number of Cd atoms present in the QD to obtain an expression for C in terms of measured values…”
Section: Theorymentioning
confidence: 99%
“…12,13 Clearly, the development of methods to investigate and monitor surfaces of PbSe QDs embedded in a sub-surface layer in such devices is of crucial importance. In this regard, positron annihilation spectroscopy (PAS) offers unique advantages over XAS, OAS and XPS, since it combines a high sensitivity to selectively probe surfaces of nanoparticles [14][15][16] with an established capacity for depth-profiling of films in the range of ~10 nm to a few m. [17][18][19] These unique merits are highly important in studies of photovoltaic devices, where charge carrier separation requires the formation of a p-n junction, 8 and PAS can probe the involved light absorbing and charge separation layers independently.…”
Section: Introductionmentioning
confidence: 99%
“…At small sizes, the surface or interface energy becomes a very significant factor in establishing not only the interior crystal structure but also the specific surface structure and ad-atom termination of the NCs. These special properties underlie the large potential of NCs for applications in areas of nanostructured thin-film solar cells [4], opto-electronics [3] and spintronics [5], fission/fusion reactor vessel steels [6], metal hydrides for hydrogen storage [7], and fluorescence-based detection of biomolecules [3].During the last decade, it has been shown that positrons (e + ) act as a sensitive, self-seeking probe of embedded and colloidal NCs [8][9][10][11][12][13][14][15][16][17][18][19][20], revealing the local structural properties and electronic structure via a measurement of the electron momentum density [21]. Positron methods are thus capable of extracting valuable information on properties at specific surface, interface or defect sites in the NCs, which are difficult to access by other methods such as transmission electron microscopy, X-ray diffraction (XRD), and EXAFS.…”
mentioning
confidence: 99%
“…Such computations have been performed for a wide variety of bulk materials [22,23]. Figure 1 shows schematically four examples of affinity profiles: (a) bcc-Cu NC embedded in Fe [8]; (b) fcc-Li NC embedded in MgO [9,10]; (c) Au NC embedded in MgO [15][16][17]; and (d) colloidal CdSe NC [11,12,14]. Calculated bulk e + affinities from Refs.…”
mentioning
confidence: 99%
See 1 more Smart Citation